METHODOLOGY FOR QUALIFYING YOUNG ATHLETES FOR THE SPORT OF KAYAKING AND CANOEING - Ibragimov Alisher Karamatovich (Proximus Journal Publishing, 2024)
in practice, the system for determining the choice and direction of sports and its components do not correlate with the peculiarities of the training of athletes at different stages, which does not allow us to look for athletes with a future and determine the direction of training, taking into account their individual specifics and issues of the training process
Keywords: selection; individual